Rehabilitation and Return to Sports after Achilles Tendon Repair - William Marrone; Robert Andrews; Aaron Reynolds; Patrick Vignona; Snehal Patel; Martin O’Malley (International Journal of Sports Physical Therapy)
Rehabilitation protocols post-Achilles tendon repair vary widely, particularly regarding weight bearing (WB) and immobilization duration, impacting recovery trajectories significantly. This commentary focuses on rehabilitation strategies following acute Achilles tendon repair (ATR), emphasizing early mobilization and progressive loading. Techniques such as blood flow restriction training (BFRT) and progressive loading to restore strength and tendon mechanical properties are discussed in the context of optimizing recovery, minimizing tendon elongation and facilitating safe return to sport (RTS). This manuscript highlights current evidence and clinical insights to guide practitioners in optimizing rehabilitation protocols for athletes recovering from ATR, aiming to improve functional outcomes and support safe return to athletic activity.